Halil Öztoprak (2012). Kur’an’da Hikmet Tarihte Hakikat ve Kur’an’da Hikmet İncil’de Hakikat - Çelik, Hasan (Journal of Alevism-Bektashism Studies, 2022)
Halil Oztoprak (2012). The Wisdom in the Qur'an is the Truth in History and the Wisdom in the Qur'an is the Truth in the Bible. Istanbul: Demos Publications. ISBN: 978-9944-387-01-1. 232 Pages.